Job Growth in Early Transition: Comparing Two Paths - Štepán Jurajda; Katherine Terrell (Institute for the Study of Labor (IZA), 2002)
Small start-up firms are the engine of job creation in early transition and yet little is known about the characteristics of this new sector. We seek to identify patterns of job growth in this sector in terms of niches left from central planning and ask about differences in job creation across two different transition economies: Estonia, which experienced rapid destruction of the pre-existing firms, and the Czech Republic, which reduced the old sector gradually. We find job growth within industries to be quantitatively more important than job growth due to across-industry reallocation. Furthermore, the industrial composition of startups is strikingly similar in the two countries. We offer convergence to "western" industry firm-size distributions as an explanation. We also find regularities in wage evolution across new and old firms, including small differences in job quality across the two transition paths.
Keywords: P5; J2; O4; P2; O1; 330; job creation; job destruction; transition economies; new sector jobs; Estonia; Czech Republic; Unternehmensgründung; Klein- und Mittelunternehmen; Betriebsgrößenstruktur; Übergangswirtschaft; Beschäftigungseffekt; Tschechische Republik; Estland